(untitled) (Swiss Medical Weekly, 2017)
PURPOSE Staphylococcus aureus bloodstream infections (SA BSI) are associated with substantial mortality. The rapid emergence of methicillin-resistant S. aureus (MRSA), known to be associated with worse outcome, may blur advances made regarding mortality attributed to SA BSI caused by methicillin-sensitive S. aureus (MSSA) strains. In the unusual setting of a very low MRSA prevalence institution, we investigated incidence, mortality and trends of BSI caused by MSSA over the last 20 years. OBJECTIVE To evaluate and demonstrate trends in incidence and mortality of MSSA BSI as well as risk factors for mortality. METHODS Retrospective, observational analysis of the prospective bloodstream infection cohort at the University Hospital Basel between January 1993 and December 2013. All patients with blood cultures positive for MSSA were included. All patients were analysed regarding pertinent demographic, clinical and antimicrobial treatment data. We calculated incidence, temporal trends and mortality of MSSA BSI. RESULTS 1328 episodes of MSSA BSI were identified, accounting for a yearly incidence ranging from 2.1 to 4.5 per 10 000 patient-days (p = 0.2 for trend). Overall mortality was 19.3% and did not improve over time. Community-acquired MSSA BSI significantly increased over time, while nosocomial cases decreased (p <0.05). CONCLUSIONS Mortality related to MSSA BSI remains high and unchanged over the last 20 years. Despite advances in treatment and supportive care in medicine during the last 20 years survival did not improve and, therefore, new approaches are required to lower mortality in MSSA BSI.